1996
DOI: 10.1136/bmj.312.7028.401
|View full text |Cite
|
Sign up to set email alerts
|

Failure to realise growth potential in utero and adult obesity in relation to blood pressure in 50 year old Swedish men

Abstract: Objectives-To clarify the type of fetal growth impairment associated with increased blood pressure in adult life, and to establish whether this association is influenced by obesity and is mediated through impairment ofinsulin action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
245
6
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(286 citation statements)
references
References 25 publications
29
245
6
6
Order By: Relevance
“…Amplification of the low birthweight effect on cardiovascular risk factors by greater weight gain in childhood and adult obesity is well recognised [4,12,14,15,[17][18][19]. In this study, waist circumference, as a marker for abdominal fat distribution and fat mass, as a marker of general fat distribution, had similar associations with the cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Amplification of the low birthweight effect on cardiovascular risk factors by greater weight gain in childhood and adult obesity is well recognised [4,12,14,15,[17][18][19]. In this study, waist circumference, as a marker for abdominal fat distribution and fat mass, as a marker of general fat distribution, had similar associations with the cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, an association between low birthweight and higher systolic and diastolic blood pressures (BP) and fasting blood glucose concentrations, but not measures of insulin sensitivity or secretion, has been reported in 20-year-old adults [11]. These observations, made in the absence of centralisation of body fat stores or frank obesity in the low-birthweight group, are of interest, as recently consideration has been given to the potential interaction between low birthweight and subsequent growth or the presence of obesity in the development of these adultonset chronic diseases [4,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A number of studies have reported that features of the chronic disease phenotype have been accentuated or amplified in the presence of postnatal or childhood skeletal catch-up growth [17,19,22,24], although this has not been a universal finding.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9]11,29 One study even showed higher SBP in taller subjects. 30 Something similar occurs in the case of DBP.…”
Section: Pulse Systolic and Diastolic Blood Pressure In Older Peoplementioning
confidence: 99%
“…1 In contrast, the evidence as to whether childhood socioeconomic circumstances and height are related to blood pressure -one of the main coronary risk factors -in adulthood has been inconsistent: some studies find a relation, 2-6 while others do not. [7][8][9][10][11][12] Some studies that have found an association between childhood social class and adult blood pressure have shown that the association decreases or disappears after adjusting for body mass index in adulthood. 3,6 Given the strong association between obesity and blood pressure, these findings suggest that obesity is the factor that mediates the relation between childhood social class and adult blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…According to the developmental origin of health and disease hypothesis, 1 this transformation may give rise to a greater risk of chronic diseases due to the mismatch between foetal programming and the subsequent environment. [2][3][4][5][6] Obesity, a potential pandemic, is becoming a serious public health issue in developing and newly developed countries such as Taiwan. Several studies have found that the prevalence of obesity has increased in the Taiwanese population.…”
Section: Introductionmentioning
confidence: 99%